(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the critical role of language in the classroom setting, highlighting how teachers and students use both verbal and non-verbal communication to construct meaning, establish relationships, and enhance learning. Language functions not only as a tool for delivering instruction but also as a means of social interaction and identity formation